2022
DOI: 10.1002/rcm.9346
|View full text |Cite
|
Sign up to set email alerts
|

Lipid extraction has tissue‐dependent effects on isotopic values (δ34S, δ13C, and δ15N) from different marine predators

Abstract: Rationale The use of sulfur isotopes to study trophic ecology in marine ecosystems has increased in the past decade. Unlike other commonly used isotopes (e.g., carbon), sulfur can better discriminate benthic and pelagic productivity. However, how lipid extraction affects sulfur isotopic values has not been assessed, despite its frequent use to remove lipid effects on δ13C values. Methods We used white muscle and liver samples from two species of sharks and skin samples from two species of pinnipeds (sea lion a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 117 publications
0
2
0
Order By: Relevance
“…Larocque et al (2021) found little to no effect of chemical lipid extraction on the δ 34 S values of salmonids muscle and fin tissues. Moreover, Riverón et al (2022) examined white muscle and liver samples from two species of sharks and skin samples from two species of pinnipeds and found that tissues with higher lipid content (e.g., shark liver) showed the greatest differences in δ 34 S values due to lipid extraction. The similar findings of our study and others suggest that the δ 34 S values of fish tissues may be broadly robust to chemical lipid extraction when they contain low amount of sulfolipids (Moradi et al 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Larocque et al (2021) found little to no effect of chemical lipid extraction on the δ 34 S values of salmonids muscle and fin tissues. Moreover, Riverón et al (2022) examined white muscle and liver samples from two species of sharks and skin samples from two species of pinnipeds and found that tissues with higher lipid content (e.g., shark liver) showed the greatest differences in δ 34 S values due to lipid extraction. The similar findings of our study and others suggest that the δ 34 S values of fish tissues may be broadly robust to chemical lipid extraction when they contain low amount of sulfolipids (Moradi et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…We used a Soxhlet apparatus with 1:1 petroleum–ether:ethyl–ether solvent mixture while Oppel et al (2010) used a 2:1 chloroform:methanol solvent following the method of Bligh and Dyer (1959). Larocque et al (2021) study of salmonid tissues also used the lipid extract of Bligh and Dyer (1959) method, though Riverón et al (2022) study applied the methods of Folch et al (1957) with an additional deionized water rinse to remove urea from elasmobranch tissues (Kim and Koch 2012).…”
Section: Discussionmentioning
confidence: 99%